Crossover from positive to negative optical torque in mesoscale optical matter - Fei Han; John A. Parker; Yuval Yifat; Curtis Peterson; Stephen K. Gray; Norbert F. Scherer; Zijie Yan (Nature Communications, 2018)
Negative optical torque has been predicted theoretically, but experimental demonstrations have been scarce. Here, the authors show that the optical torque in a mesoscopic optical matter array can be reversed depending on number, separation and configuration of nanoparticles in a circularly polarized optical trap.